Project-Based Learning Implementation in a Participative Planning Course: Strategies, Outcomes, and Challenges - Noor, Agus Hasbi; Nurhayati, Sri (CAHAYA PENDIDIKAN, 2023)
The principal aim of this research was to understand the strategies employed in Project Based Learning (PBL) implementation in higher education setting, evaluate its impact on students' learning experiences, and pinpoint challenges faced during its application. Employing a case study method, insights were derived from in-depth examinations of specific PBL implementations within the course, facilitated by structured interviews, observation, and document analysis. The research participants are two lecturers and twenty students. The lecturers were chosen for their extensive experience in PBL implementation, while the students were purposively selected to ensure diversity in terms of academic performance, gender, and previous exposure to PBL. Thematic analysis was employed as the methodological framework for scrutinizing and interpreting qualitative data sourced from in-depth interviews and observational data. Key findings highlight the critical importance of a structured PBL introduction, the essence of real-world application through fieldwork, and the central role of collaboration, especially leveraging modern digital platforms. While the benefits of PBL in enhancing conceptual grasp and promoting soft skills development were evident, challenges, notably in team dynamics, resource provision, and the inherent unpredictability of real-world tasks, were also brought to the fore. By aligning the insights from the Participative Planning course with established PBL literature, the study illuminates the universal principles of PBL and their associated challenges. Conclusively, the paper underscores PBL's potency as a transformative pedagogical tool, emphasizing the necessity for informed strategies, adaptability, and iterative refinement for its efficacious implementation in diverse educational contexts.